Sahala dalam Praksis Sosial: Konstruksi Religiusitas dalam Pelayanan Bala Keselamatan Perspektif Sosiologi Agama - Mikael (Kelompok Studi Mitra Skolastikat MSC PinelengINELENG, 2026)
This study aims to analyze the construction of religiosity through the concept of Sahala in the Salvation Army's social service practices. This study is motivated by the shift in religiosity paradigm from a normative approach to contextual social praxis. The research employed a qualitative approach with a case study design. Data were obtained through semi-structured interviews, limited participant observation, and documentation of leaders and active servants selected through purposive and snowball sampling. Data analysis was conducted using the interactive model of Miles, Huberman, and Saldaña. The results indicate that Sahala is defined as a living faith manifested in concrete social actions. Religiosity is formed through repeated service practices as an arena of social construction, where faith values ​​are externalized in actions, objectified in community culture, and internalized as individual identity. This practice strengthens social solidarity and encourages transformative church service. This research contributes to integrating Sahala theology into the sociology of religion perspective, while emphasizing the importance of social service as a concrete expression of faith in community life.